2012
DOI: 10.2478/v10222-011-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Silico Prediction Possibility of Epitope Sequences Using Experimental Data Concerning Allergenic Food Proteins Summarized in BIOPEP Database.

Abstract: The aim of the study was to evaluate the possibility of predicting potential epitope sequences and location in allergenic proteins from food using EVALLER program by comparison with experimental epitopes summarised in the BIOPEP database of allergenic proteins. Sequences of experimental epitopes from food allergens, present in the BIOPEP database of allergenic proteins were used in the study. Sequences of potential epitopes were found using EVALLER program. The Positive Predictive Value (PPV) has been used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…The peptide TTYY possessing strong ABTS• + scavenging capacity was not detected in our samples. The sequences identified in this study (Table ) were submitted to BIOPEP (http://www.uwm.edu.pl/biochemia) and BioPD CMBI (http://biopd.bjmu.edu.cn) databases. In the first database only the antioxidant peptide LLPHHADADY (ID 3807) was found.…”
Section: Resultsmentioning
confidence: 99%
“…The peptide TTYY possessing strong ABTS• + scavenging capacity was not detected in our samples. The sequences identified in this study (Table ) were submitted to BIOPEP (http://www.uwm.edu.pl/biochemia) and BioPD CMBI (http://biopd.bjmu.edu.cn) databases. In the first database only the antioxidant peptide LLPHHADADY (ID 3807) was found.…”
Section: Resultsmentioning
confidence: 99%
“…6,29,30 We have recently demonstrated that they are transferred from the apical to the basolateral chamber of a monolayer of Caco2 cells grown in a bicameral system and that the basolateral solution where they were detected inhibits the activity of HMGCoAR. 33 BIOPEP (www.uwm.edu.pI/biochemia) 34 is an open access database enabling to hypothesize the potential biological activities of peptides based on the presence of some specific amino acid sequences. A screening of the structures of these soy or lupin peptides with BIOPEP suggested that their structures were compatible with a potential function as DPP IV inhibitors.…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Since the concentration of Ge in the mixture solution could not be determined directly, finding a way to determine the concentration of Ge became a key point to calculate the separation degree. There are many reports about determining the concentration of a substrate in a mixture that displays disturbance in the concentration determination,25–27 among which double‐wavelength spectroscopy is one of the common ways 28, 29. However, to determine the concentration of a substrate by double‐wavelength spectroscopy the components under test in the mixture should not take place in any reaction.…”
Section: Resultsmentioning
confidence: 99%